Design patent classification for changes in automotive interior design paradigm - Wonjoon Yoon; Jieun Kim (Journal of Intellectual Property)
This study aims to develop a design patent classification reflecting multimodal design elements and design trend changes of automotive interiors. Following the development process of the Locarno classification, a proposed design classification consisting of 96 level-4 design elements with a four-depth matrix structure was developed in collaboration with automotive interior designers and a design patent expert. To validate the effectiveness of the proposed design classification and to identify the classification requirements of core user groups, an online survey was conducted among automotive interior designers, IP data analysts, design patent examiners, and patent attorneys. Through a comparison with the Locarno classification for validation, results showed that the proposed design classification received higher scores for both usability(mean 3.94 vs 2.28) and taxonomic(mean 4.35 vs 2.65) entries. In particular, from the usability perspective, the application of the multimodal design concept was positively evaluated by practitioners, and from a taxonomic perspective, a more granular classification system was also positively evaluated. Although there were different opinions among the core user groups, it was improved overall. Thus, it has the potential to play an essential role in applying design classifications to new trends in automotive interior design caused by the emergence of converged products.